Effects of Cr Substitution on Negative Thermal Expansion and Magnetic Properties of Antiperovskite Ga1−xCrxN0.83Mn3 Compounds - Guo, Xinge; Tong, Peng; Lin, Jianchao; Yang, Cheng; Zhang, Kui; Lin, Shuai; Song, Wenhai; Sun, Yuping (Frontiers in Chemistry, 2018)
Negative thermal expansion (NTE) and magnetic properties were investigated for antiperovskite Ga1-xCrxN0.83Mn3 compounds. As x increases, the temperature span (ΔT) of NTE related with Γ5g antiferromagnetic (AFM) order is expanded and shifted to lower temperatures. At x = 0.1, NTE happens between 256 K and 318 K (ΔT = 62 K) with an average linear coefficient of thermal expansion, αL = -46 ppm/K. The ΔT is expanded to 81 K (151 K- 232 K) in x = 0.2 with αL = -22.6 ppm/K. Finally, NTE is no longer visible for x ≥ 0.3. Ferromagnetic order is introduced by Cr doping and continuously strengthened with increasing x, which may impede the AFM ordering and thus account for the broadening of NTE temperature window. Moreover, our specific heat measurement suggests the electronic density of states at the Fermi level is enhanced upon Cr doping, which favors the FM order rather than the AFM one.